FRAMEWORK FOR THE SUSTAINABILITY OF HOUSING CO-OPERATIVES IN SOUTH AFRICA - Kobus VAN WYK; Richard JIMOH (Journal of Construction Project Management and Innovation)
The current difficulties in obtaining credit for housing, following the global economic crisis, show that private individual home-ownership is not effective enough in addressing the housing needs of the low and middle income groups. As a result of this and coupled with the limited studies in South Africa on co-operative housing at that time, the need to find an option that will solve the housing needs of the people became intense. The study developed a framework for the sustainability of housing co-operatives through the administration of 176 self-addressed structured questionnaires to housing co-operatives based on the strategies identified from literature. The data was analysed using mean score and Cronbach’s Reliability Coefficient Test. Based on the findings, framework for sustainable housing co-operatives in South Africa was developed from the strategies. The strategies were categorised into the following factors: policy and legislation; support services; education, training and information; and governance. The framework developed has practical relevance to government officials in the Department of Human Settlements at the Municipal, Provincial and National level in terms of policy formulation in areas of co-operative housing subsector and also the various housing co-operatives in the area of governance of their members. Apart from these categories, the roles to be played by organisations such as South Africa Housing Co-operatives Association (SAHCA), Housing Development Agency, Social Housing Regulatory Agency and financial institutions were enunciated.